Prevalence of epilepsy in Rwanda: a national cross-sectional survey. - Simms, V; Atijosan, O; Kuper, H; Nuhu, A; Rischewski, D; Lavy, C (2008)
OBJECTIVE: To estimate the prevalence of epilepsy in Rwanda, as part of a survey of musculoskeletal impairment (MSI). METHODS: Cross-sectional nationally representative survey. Clusters of 105 people were selected with probability proportional to size, using the 2002 national census as the sampling frame. Within each cluster, 80 people were selected through compact segment sampling. Physiotherapists examined all participants using a standard questionnaire to assess the presence of seizures through self-report, as well as aetiology, treatment needs and severity of the seizures. Health-related quality of life was assessed using the EuroQol generic health index (EQ5D). RESULTS: The response rate was 80.8%, with 6757 individuals screened. The estimated prevalence of epilepsy was 0.7% (95% confidence intervals 0.5-0.9%). A quarter (23%) of cases reported that onset of epilepsy was at birth, for 32% onset was between birth and age 5, 23% between ages 5 and 16, and 21% above the age of 16. In 4.3% of people with epilepsy, an accident during a seizure caused permanent MSI, as identified by a case history and physical examination. The majority of people with epilepsy (59.6%) had never received medical treatment for it. Epilepsy was associated with a significantly reduced quality of life. CONCLUSIONS: Epilepsy is a significant and neglected health problem in Rwanda at all ages. Investing in treatment for epilepsy would prevent some disability causing accidents from occurring.